Hubungan Imunoekspresi Î²-Catenin antara Karsinoma Sel Skuamosa Oral Derajat Rendah dan Derajat Tinggi Berdasarkan Sistem Grading Bryne. - Welly Hartono Ruslim; Ening Krisnuhoni; Kusmardi Suid (Majalah Patologi Indonesia, 2015)
Background Î²-catenin is an important protein in cellular adhesion and signal transduction. In unstimulated condition, Î²-catenin only appears on the cellular membrane. Altered expression of Î²-catenin has been associated with progressiveness and metastatic process of malignancy in human. The aim of this study was to evaluate the expression of Î²-catenin on oral squamous cell carcinoma (OSCC) and also to assess its different expression in low grade and high grade lesions based on Bryne grading system. Methods This study was conducted on 2 groups of OSCC which included 20 cases of low grade and 20 cases of high grade. Immunohistochemistry staining of Î²-catenin was used to identify the difference of its expression in cell membrane, cytoplasm, and nuclei on invasive tumor front. Results The expression of Î²-catenin on cell membrane, cytoplasm, and nuclei showed significant difference between low and high grade OSCC (p=0.000; p=0.005; and p=0.035, respectively). There has not been any significant association between Î²-catenin expression with age, sex, and tumor location. Conclusion Expression of Î²-catenin could showed morphological change the OSCC. Key words : Î²-catenin, Bryne grading, oral squamous cell carcinoma (OSCC).